Statistical analysis of corrosion failures in hearing aid devices from tropical regions. (December 2021) - Yadav, Abhijeet; Gupta, Kapil Kumar; Ambat, Rajan; Christensen, Morten Løgstrup
Highlights: Hearing aid devices are prone to corrosion failures from tropical regions due to harsh climatic conditions. Corrosive media such as KOH and human sweat were the primary cause for corrosion failures. Various corrosion mechanisms such as ECM, galvanic corrosion, and localized corrosion led to the failure of HA components. Microphones are the most vulnerable component to corrosion failure and showed highest failure percentage. The failed HA devices from tropical regions showed higher failure rate during summer season. Abstract: Corrosion reliability of hearing aid (HA) devices is a critical issue due to their exposure to harsh climatic conditions like high humidity and temperature, along with the combination of high level of salt contamination from human sweat and environmental pollutants. Statistical analysis of corrosion failure data can provide a better understanding of the failure sequence and cause, which is important as the issue is due to multiple parameter effects on a complex device consisting of many components. In this study, root cause failure analysis of the failed hearing aid devices used in the tropical regions was performed using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Analysis was used for understanding the failure mechanisms, while the data was used for statistical analysis in order to elucidate the device degradation rate and failure probability. Potassium hydroxide (KOH) electrolyte leakage from faulty Zn-air batteries (ZABs) and human sweat were prominent causes for the corrosion failure of hearing aid components. The rate of corrosion failures was found to accelerate during the summer season due to an increase in human perspiration rate and the release of KOH electrolyte from the batteries.